2008
DOI: 10.1080/07399330701876521
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study Examining Psychosocial Distress, Coping, and Social Support Across the Stages and Phases of Epithelial Ovarian Cancer

Abstract: Ovarian cancer patients experience high levels of anxiety and depression, yet there is little research regarding coping and support of this population. In this study we examined the experiences of women during diagnosis and treatment via 30 semistructured interviews. The interviews were analyzed qualitatively, and five main themes were evident: (1) extreme blunting; (2) having a "forgotten cancer"; (3) traumatic surprise of diagnosis; (4) highs and lows of health care; and (5) support gap experienced postdiagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 12 publications
7
54
0
Order By: Relevance
“…Zabora, Brintzenhofeszoc, Curbow, Hooker, and Piantadosi (2001) reported that approximately 20% of these patients experience a significantly elevated level of distress after a new diagnosis. Psychosocial distress has also been noted for women during the screening process for ovarian cancer, during the diagnosis and treatment phase of illness, and at times of recurrence (Kornblith et al, 1995;Petersen, Graham, & Qunlivan, 2005;Power, Brown, & Ritvo, 2008;Robinson, Rosen, & Bradley, 1997). High levels of anxiety and depression have been reported during chemotherapy treatment (Guidozzi, 1993;Kornblith et al) with high distress scores continuing for one third of the long-term survivors of ovarian cancer (Ersek et al, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Zabora, Brintzenhofeszoc, Curbow, Hooker, and Piantadosi (2001) reported that approximately 20% of these patients experience a significantly elevated level of distress after a new diagnosis. Psychosocial distress has also been noted for women during the screening process for ovarian cancer, during the diagnosis and treatment phase of illness, and at times of recurrence (Kornblith et al, 1995;Petersen, Graham, & Qunlivan, 2005;Power, Brown, & Ritvo, 2008;Robinson, Rosen, & Bradley, 1997). High levels of anxiety and depression have been reported during chemotherapy treatment (Guidozzi, 1993;Kornblith et al) with high distress scores continuing for one third of the long-term survivors of ovarian cancer (Ersek et al, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While some qualitative research has been completed (e.g., Ekman et al, 2004;Ferrell, Smith, Cullinane, et al, 2003;Power et al, 2008), there is very little quantitative, especially around whether or not people want help with their needs. This initial study is useful for pinpointing areas of concern and identifying potential areas for future research and development of interventions.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19] While elevated levels of stress and anxiety are common among cancer patients in general, levels of distress among those with lung cancer are nearly always higher than all other cancer sites. [20,21] In a study by Zabora et al including over 4,400 patients comparing 14 different cancer sites, the prevalence of distress was found to be highest among lung cancer patients (43.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Development of self-management skills is particularly urgent for women with ovarian cancer as frequent recurrence, limited treatment options, and an often short prognosis abruptly propel these women into a period of intense transitions (Power, Brown, & Ritvo, 2008). Transitions, or passages between two relatively stable periods of time during which an individual moves from one life phase, situation, or status to another (Schumacher, Jones, & Meleis, 1999), are times of vulnerability to risks that may influence health and well-being (Davies, 2005).…”
mentioning
confidence: 99%